Montelukast Use and Patterns of Ambulatory Care among Asian versus Non-Asian Adult Patients with Asthma and/or Allergic Rhinitis in the United States - Joseph Vasey; Shalini Bagga; Huan Huang; Tongsheng Wang; David Thompson (Journal of Health Economics and Outcomes Research)
**Background:** Asthma and allergic rhinitis (AR) are inflammatory conditions that are similar in pathophysiology. Mild-to-moderate persistent asthma has been widely treated with inhaled corticosteroids, while allergic rhinitis is commonly treated with antihistamines, nasal corticosteroids, anticholinergics, and other allergy specific medications. The introduction of montelukast, a leukotriene receptor antagonist, has opened a treatment pathway that is common to both conditions. Previous real world studies of montelukast (Singulair®) relative to other medications have not investigated the role of race in the management of asthma and AR, specifically as relates to differences among Asian versus non-Asian patients.